2018
DOI: 10.1038/s41598-018-19221-4
|View full text |Cite
|
Sign up to set email alerts
|

Parturition in baboons (PAPIO SPP.)

Abstract: The Old World non-human primates (NHP) - baboons (Papio spp.) share similarities with humans regarding fetal and placental development and some pregnancy-related complications. Information about the mechanism of birth and complications arising during parturition in these species is relatively sparse. In this manuscript, we add information from a series of pathological and observational cases to highlight insights and selected complications of birth in Papio spp, based on video-recording of the delivery process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Nevertheless, instances of obstructed labour have been reported for both diminutive marmosets and small‐bodied squirrel monkeys ( Saimiri sciureus ) (Abee, 1989 ; Debyser, 1995 ) as well as medium‐sized macaques ( Macaca mulatta and M. fascicularis ) and baboons ( Papio spp.) (Schultz, 1949 ; Schlabritz‐Loutsevitch et al ., 2018 ). A study on a large sample of captive pigtailed macaques ( Macaca nemestrina ) reported a surprisingly high incidence of difficult births at 14%, while in some captive squirrel monkey populations the occurrence may be as high as 50% (Bowden, Winter & Ploog, 1967 ; Stockinger et al ., 2011 ).…”
Section: The Birth Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, instances of obstructed labour have been reported for both diminutive marmosets and small‐bodied squirrel monkeys ( Saimiri sciureus ) (Abee, 1989 ; Debyser, 1995 ) as well as medium‐sized macaques ( Macaca mulatta and M. fascicularis ) and baboons ( Papio spp.) (Schultz, 1949 ; Schlabritz‐Loutsevitch et al ., 2018 ). A study on a large sample of captive pigtailed macaques ( Macaca nemestrina ) reported a surprisingly high incidence of difficult births at 14%, while in some captive squirrel monkey populations the occurrence may be as high as 50% (Bowden, Winter & Ploog, 1967 ; Stockinger et al ., 2011 ).…”
Section: The Birth Processmentioning
confidence: 99%
“…Yet, in a captive colony of pigtailed macaques, most birth difficulties turned out to be due to malpresentation, particularly breech positions (Stockinger et al ., 2011 ). Breech presentations were also found to be a major cause (25%) of dystocic births in baboons (Schlabritz‐Loutsevitch et al ., 2018 ), and they seem to explain most birth difficulties in squirrel monkeys and other non‐human primates (Bowden et al ., 1967 ; Stoller, 1995 ).…”
Section: The Birth Processmentioning
confidence: 99%
“…; Schlabritz‐Loutsevitch et al. ). In humans, 30% of brain development takes place in utero compared to 60% in NHPs, including baboons (DeSilva and Lesnik ; DeSilva ).…”
Section: Discussionmentioning
confidence: 99%
“…Temporal cortex tissue samples were collected immediately from fetuses of control and MNR mothers at 120, 140, and 165 days gestational age (dGA, length of gestation is 163–185 dGA (Schlabritz‐Loutsevitch et al. )) and flash frozen and stored at −89°C until analyzed (Schlabritz‐Loutsevitch et al. ) (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The infrahyoid muscles are also markedly small in infants (Figure 7). Moreover, hypotonia itself has been suggested to be a risk factor for NBPP (Abzug et al, 2019;Abzug & Kozin, 2014;Defrancesco et al, 2019 (Abitbol, 1996;Kavanagh et al, 2011;Rosenberg & Trevathan, 1995;Schlabritz-Loutsevitch et al, 2018;Stockinger et al, 2011)…”
Section: Head Size Neck Muscle Strength and Tonementioning
confidence: 99%